‘The Book of Hours’ and Adaptation, Medievalism and Genre: Is Young Adult Medieval Fiction Merely the Fan Fiction of History? - Sidebottom, Tara (Curtin University, 2022)
Fan fiction methodologies and medievalism can be merged with the conventions of Young Adult fiction to construct fictional narratives that experiment with combinations of history, fiction, and myth in processes of adaptation. This confluence of creative processes is fuelled by a reader-writer’s desire for a narrative that meets their precise textual preferences. This thesis explicates the combination of both creative processes within Young Adult fiction through creative practice, titled 'The Book of Hours'.